2010
DOI: 10.1074/jbc.m109.073932
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of p21/CIP1 Cell Cycle Inhibitor by PDEF Controls Cell Proliferation and Mammary Tumor Progression

Abstract: The Ets family of transcription factors control a myriad of cellular processes and contribute to the underlying genetic loss of cellular homeostasis resulting in cancer. PDEF (prostate-derived Ets factor) has been under investigation for its role in tumor development and progression. However, the role of PDEF in cancer development has been controversial. Some reports link PDEF to tumor promoter, and others show tumor-suppressing functions in various systems under different conditions. So far, there has been no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 42 publications
(29 reference statements)
0
34
2
2
Order By: Relevance
“…The data obtained from functional assays further confirm the findings and provide new insights into the role of PDEF in regulating the prostate cancer process associated with STMN. PDEF has been studied in our laboratory as a tumor suppressor (16) and with the use of iTRAQ labeling and mass spectrometric analysis techniques we were able to shed light on a possible role of PDEF in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The data obtained from functional assays further confirm the findings and provide new insights into the role of PDEF in regulating the prostate cancer process associated with STMN. PDEF has been studied in our laboratory as a tumor suppressor (16) and with the use of iTRAQ labeling and mass spectrometric analysis techniques we were able to shed light on a possible role of PDEF in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…Our previous in vitro and in vivo data prove that PDEF is a tumor suppressor in breast cancer cells. We showed that PDEF-expressing cells block the cell growth rate, and this retardation was reversed when PDEF expression was silenced with PDEF-specific small interfering RNA (16). Upon STMN expression PDEF overexpressing cells show increased growth potential in an MTT proliferation assay in both PC3 (Fig.…”
Section: Relevance Of Stmn To the Prostate Cancer Progression Processmentioning
confidence: 97%
See 1 more Smart Citation
“…To determine the effect of overexpression of maspin and cysteine mutations on the tumorigenic properties of TM40D cells, we assessed the anchorage-independent growth and in vitro proliferation of WT and mutant maspin TM40D cells using soft agar colony formation and MTT assays, respectively. Anchorage-independent growth is one of the hallmarks of transformation, and the soft agar assay is a commonly used in vitro assay for detecting malignant transformation of cells (28,37). The abilities of the cells to form colonies on soft agar are shown in Fig.…”
Section: Cysteine Residues Affect Cell Proliferation Pattern Of Tm40dmentioning
confidence: 99%
“…The cells were lysed 36 h after transfection, and assays were performed (19,20) using the Promega Dual-Luciferase reporter assay system (catalog no. E1910) according to the manufacturer's instructions.…”
Section: Figure 2 Jaz Interacts With Sirt1mentioning
confidence: 99%